1992
DOI: 10.1080/01635589209514180
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical and oral L‐selenomethionine on pigmentation and skin cancer induced by ultraviolet irradiation

Abstract: This study was conducted to determine whether oral and/or topical selenium (Se) supplementation can reduce the incidence of acute and/or chronic damage to the skin (i.e., sunburn and pigmentation and/or skin cancer, respectively) induced by ultraviolet (UV) irradiation in mice. Groups of 38 BALB:c female mice or 16 Skh:2 hairless pigmented mice were treated with 1) lotion vehicle, 2) 0.02% L-selenomethionine (SeMet) lotion, or 3) vehicle and 1.5 ppm SeMet in the drinking water. Within each group, 30 BALB:c mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…These results reflected the inverse associations observed between serum selenium concentrations and overall incidence of persons newly affected by BCC and SCC, although mostly these associations did not reach statistical significance. This apparently protective effect of selenium on skin cancer incidence is consistent with in vivo and in vitro studies that have shown that topical and oral selenium can provide protection against ultraviolet-induced sunburn, tanning, and skin cancer (7,(25)(26)(27). Previous human data are sparse and conflicting, however.…”
Section: Discussionsupporting
confidence: 60%
“…These results reflected the inverse associations observed between serum selenium concentrations and overall incidence of persons newly affected by BCC and SCC, although mostly these associations did not reach statistical significance. This apparently protective effect of selenium on skin cancer incidence is consistent with in vivo and in vitro studies that have shown that topical and oral selenium can provide protection against ultraviolet-induced sunburn, tanning, and skin cancer (7,(25)(26)(27). Previous human data are sparse and conflicting, however.…”
Section: Discussionsupporting
confidence: 60%
“…In the mouse model, a significant reduction in the formation of 8-oxo-2 ¶-deoxyguanosine, an oxidative DNA damage biomarker, was observed in UV radiation -and arsenic-treated mice that were supplemented with selenium compared with those treated with UV radiation or arsenic alone (51). The initiation of UV radiation -induced skin tumors has been shown to vary with the activity of glutathione peroxidases and thioredoxine reductases (52).…”
Section: Discussionmentioning
confidence: 99%
“…These epidemiology studies have generated both positive and negative results, but do provide substantial support for the hypothesis that Se compounds have cancer preventive activity (Combs, 2005). In recent years, numerous investigators have reported inverse associations between Se biomarkers (toenail Se or serum Se levels) and the risk of neoplasia in several sites, including the prostate (van den Brandt et al, 2003, Vogt et al, 2003, Li et al, 2004, esophagus and gastric cardia (Wei et al, 2004), liver (Sakoda et al, 2005), colon (Ghadirian et al, 2000;Jacobs et al, 2004;Peters et al, 2006), lung (van den Brandt et al, 1993, Zhuo et al, 2004, skin (Burke et al, 1992), and urinary bladder (Zeegers et al, 2002). It should be noted, however, other studies have found no association between Se status and the risk of cancer of the breast (Dorgan et al, 1998;Ghadirian et al, 2000;Männistö et al, 2000), prostate (Ghadirian et al, 2000;Allen et al, 2004), ovary (Pan et al, 2004), non-cardiac stomach (Wei et al, 2004), urinary bladder (Michaud et al, 2002), or lung (Mahabir et al, 2006).…”
Section: Introductionmentioning
confidence: 99%